ONCE AGAIN ABOUT THE CUSTOM OF “UCHA” (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The Kyrgyz still have an archaic custom of the prestigious distribution of bootycalled “ucha” - or the back of the carcass of a ram, horse. This custom of distribution of prey iswidespread among the Turkic-speaking and Tungus-speaking peoples of Siberia. The essence ofthe custom of “teaching” was the distribution of part of the booty to their fellow tribesmen. Thisexclamation provided for the allocation of an honorable part of the extracted meat to anyone whomet. A Kyrgyz hunter, having met someone riding with prey, at the word “snake” took the hindleg with part of the spine and the skin, the second and third oncoming ones also cut off the bestpieces of meat for themselves, as a result, the hunter is left with nothing. A similar custom called“ucha ber!” (lit. give the sacrum) was registered among the Khakass and Altaians. For example,in the Northern Altai, the owner of the yurt presented the best part of the meat “teaching” as a giftto the shaman, “who, having accepted, cuts off the pulp, but not all, and gives it to any honorable person he wants. This one, cutting himself off, passes on to another, usually an older relative ora stranger, who, having cut himself off, gives to everyone who is, and immediately the bones arefinally cleansed “teaching”, without damaging them. The archaic custom of “learning” and thedistribution of a share called “keshik” existed and continues to exist among modern Kyrgyz. Inthe Kyrgyz language, the word “keshik” denotes the remnants of food and drink from the table ofnoble and honored guests, which are treated to young people or neighbors, as well as the gift itselffrom the treats at the feast. Thus, the custom of “learning” arose among hunters and originatesfrom hunting trades, because “an equalizing law came into force, going back to the norms of collective production and consumption of the tribal system. The Kyrgyz had an equal division of prey,regardless of the contribution of any member of the hunting artel. Otherwise, the mountain hostscould get angry and not give good luck next time. According to scientists, the conditions for theoperation of the custom of “learning” arose during the period of decomposition of the tribal systemand the emergence of a neighboring community, when the exclusive right of members of the clanto tribal territories began to be violated, it seems more reliable to assume that it arose during primitive tribal relations. The custom of “teaching” guaranteed people support in case of need, becauseit determined the development of mutual assistance, improved the system of marriage ties and theestablishment of social gradations.
Keywords: teaching tartuu, shyralga, kyrgyz, ethnos, kyrgyz customs, ethnic culture, traditions.